Is Isaac without Ishmael complete?: a nineteenth-century debate re-visited - Bennett, Clinton (Islam and Christian-Muslim relations, 1991)
Biblical passages which Christians have traditionally applied to Islam, predicting the rise of false prophets and of false Christs, inform negative judgements. The theory of one nineteenth-century writer, Charles Forster (1787-1871) is examined as possibly offering a sympathetic Biblical-key in its interpretation of God's promise to Abraham that he would bless Ishmael and make him father of a great nation. Islam, Forster argued, fulfilled this promise: permitted to exist by God, Islam's eventual "bringing in" to the Kingdom would be by divine not human action. This raises questions about the propriety of proselytizing Muslims and suggests that theological disputation might yield to mutual striving to "do good works" or to obey God's will (Q.5:48; Matt 7:21).